Perlindungan Etik Profesi Dokter dalam Pelayanan on Call: Antara Kewajiban Moral, Risiko Hukum dan Hak Pasien - Dita Rosalia Arini; Uta Provinsiana Sukmara (CV. ITTC INDONESIA, 2026)
On-call doctor practice is a form of healthcare service that arises from the moral obligation of the medical profession to always be ready to provide assistance, even outside of formal working hours. On the other hand, this practice carries legal vulnerabilities for doctors due to the lack of detailed regulations regarding the scope of responsibility, while patients' rights must still be fully upheld. This study aims to analyze the position of the moral obligation of doctors in on-call practice from an ethical perspective, examine the implications of their legal responsibilities in civil, criminal, and professional disciplinary domains, and formulate a framework for ethical protection of the medical profession that is proportional while still fulfilling patients' rights. The research uses a normative juridical method with a legislative, conceptual, and case approach, through the review of laws and regulations, the Indonesian Medical Code of Ethics, court decisions, and relevant scientific literature. The findings indicate that the moral obligation of on-call doctors transforms into a legal duty (duty of care) once active contact with a patient occurs, with responsibilities that can be divided in a tiered manner between individual doctors and hospital institutions based on the theory of limited liability and the non-delegable duty doctrine. A proportional ethical protection framework for the medical profession can be formulated through three pillars: the application of the principle of ultimum remedium in criminal law, strengthening documentation obligations as an evidentiary instrument, and enhancing the role of ethical and disciplinary forums in assessing the appropriateness of medical actions in a contextual manner. This framework is expected to serve as a reference for professional organizations, healthcare facilities, and policymakers in developing fair guidelines for on-call doctor practices.